The Cone Opsin Repertoire of Osteoglossomorph Fishes: Gene Loss in Mormyrid Electric Fish and a Long Wavelength-Sensitive Cone Opsin That Survived 3R. (27th December 2018) - Liu, Da-Wei; Wang, Feng-Yu; Lin, Jinn-Jy; Thompson, Ammon; Lu, Ying; Vo, Derek; Yan, Hong Young; Zakon, Harold
Abstract: Vertebrates have four classes of cone opsin genes derived from two rounds of genome duplication. These are short wavelength sensitive 1( SWS1 ), short wavelength sensitive 2( SWS2 ), medium wavelength sensitive ( RH2 ), and long wavelength sensitive ( LWS ). Teleosts had another genome duplication at their origin and it is believed that only one of each cone opsin survived the ancestral teleost duplication event. We tested this by examining the retinal cones of a basal teleost group, the osteoglossomorphs. Surprisingly, this lineage has lost the typical vertebrate green-sensitive RH2 opsin gene and, instead, has a duplicate of the LWS opsin that is green sensitive. This parallels the situation in mammalian evolution in which the RH2 opsin gene was lost in basal mammals and a green-sensitive opsin re-evolved in Old World, and independently in some New World, primates from an LWS opsin gene. Another group of fish, the characins, possess green-sensitive LWS cones. Phylogenetic analysis shows that the evolution of green-sensitive LWS opsins in these two teleost groups derives from a common ancestral LWS opsin that acquired green sensitivity. Additionally, the nocturnally active African weakly electric fish (Mormyroideae), which are osteoglossomorphs, show a loss of the SWS1 opsin gene. In comparison with the independently evolved nocturnally active South American weakly electric fish (Gymnotiformes) with a functionally monochromatic LWS opsin cone retina, the presence of SWS2, LWS, and LWS 2 cone opsins in mormyrids suggests the possibility of color vision.